2021
DOI: 10.1016/j.heliyon.2021.e07200
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-A1 and the sheddase ADAM12 are upregulated in COVID-19

Abstract: More than 3.5 million people have died globally from COVID-19, yet an effective therapy is not available. It is, therefore, important to understand the signaling pathways that mediate disease progression in order to identify new molecular targets for therapeutic development. Here, we report that the blood serum levels of ephrin-A1 and the sheddase ADAM12 were significantly elevated in COVID-19 patients treated at SUNY Downstate Hospital of Brooklyn, New York. Both ephrin-A1 and ADAM12 are known to be involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The ADAM12 receptor and ephrin-A1, one of the ADAM12 substrates, play a role in inflammation and endothelial cell permeability. Among COVID-19 patients, some had significantly elevated concentrations of ADAM12 and ephrin-A1 in their blood serum, with critical patients having the highest levels[ 58 ]. Therefore, the inflammatory response mediated by Ephrin-A1 may be one of the major factors in the morbidity and mortality related to COVID-19.…”
Section: Adamalysinsmentioning
confidence: 99%
“…The ADAM12 receptor and ephrin-A1, one of the ADAM12 substrates, play a role in inflammation and endothelial cell permeability. Among COVID-19 patients, some had significantly elevated concentrations of ADAM12 and ephrin-A1 in their blood serum, with critical patients having the highest levels[ 58 ]. Therefore, the inflammatory response mediated by Ephrin-A1 may be one of the major factors in the morbidity and mortality related to COVID-19.…”
Section: Adamalysinsmentioning
confidence: 99%
“…In summary, using the SPECS method, quantitative proteomics, and biochemical approaches, we discovered many ADAM12S-regulated downstream targets in the cultured medium of gastric cancer cells and elucidated a novel mechanism by which ADAM12S promotes the migration of gastric cancer cells. Previous and recent clinical experiments revealed that ADAM12 was highly expressed in the tissue, serum, and urine of cancer patients or other diseases, including COVID-19 patients . Therefore, the discovery of the biological function and the signaling pathways that ADAM12 is involved in may help us to assess the therapeutic value of this protein and its associated signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous and recent clinical experiments revealed that ADAM12 was highly expressed in the tissue, serum, and urine of cancer patients or other diseases, including COVID-19 patients. 53 Therefore, the discovery of the biological function and the signaling pathways that ADAM12 is involved in may help us to assess the therapeutic value of this protein and its associated signaling pathways.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In parallel, its impact in every step of carcinogenesis has been increasingly documented [ 1 , 12 , 13 ]. It has even been proposed as a potential treatment target for COVID-19 infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%